ND3 Mitochondrial Polimorphism G-10399-A and C-10401-T Significantly Associated with Elevated Serum 8-OHDG Concentration and Increased Risk of Malignant Behavior in Breast Cancer - Wayan Tianing (Journal of Global Pharma Technology, 2017)
Introduction: ND3¬ gene polymorphisms had been associated with the risk of breast cancer. However, it association with cancer cell behavior and progression is yet to be evaluated and thus this research evaluate the relationship between ND3 gene polymorphisms with 8-OHdG concentration that represent oxidative DNA damage and with the risk of malignant cancer behavior. Method: A case-control study was conducted in Faculty of Medicine Udayana University and Sanglah General Hospital from January to December 2016. The case group was defined as sample with lymph vascular invasion and histological grade III. The blood samples were obtained to evaluate the polymorphism and serum 8-OHdG concentration. The polymorphisms were detected using PCR and sequencing while serum 8-OHdG concentration was determined using ELISA. Result: 70 subjects were enrolled in this study with 35 samples for each group. Increased serum 8-OHdG were associated with the presence of ND3 polymorphism [375.37±203.56ng/mL in wild type vs 610.65±271.9ng/mL (G-10399-A) and 636.18±287.75ng/mL (C-10401-T); p<0.05] and the number of polymorphism [391.45±210.97ng/mL for no polymorphism vs 487.52±227.18ng/mL in one polymorphism and 861.36±253.27ng/mL for two polymorphism; p<0.05]. Finally, the presence of polymorphism increased the risk of more malignant cancer behavior (OR: 4.792; 95%CI: 1.741 – 13.188). Conclusion: G-10399-A and C-10401-T ND3 polymorphism clearly increased oxidative DNA damage and the risk of malignant cancer behavior in breast cancer patients.Keywords: ND3 gene polymorphism G-10399-A and C-10401-T, 8-OHdG, malignant behavior, breast cancer